EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN ISK DI INSTALASI FARMASI PASIEN RAWAT INAP DI RS EFARINA ETAHAM PEMATANG SIANTAR PERIODE JANUARI-MARET TAHUN 2024 - Sabar Kristian Nazara; Isma Oktadiana, Octavian Nababan (CV. ADIBA AISHA AMIRA, 2025)
Urinary tract infection (UTI) is the growth of microorganisms in the urinary tract, which is normally sterile. Antibiotics are the most widely used drugs worldwide due to the high incidence of bacterial infections. Women are more prone to UTIs than men because the female urethra is shorter, making it easier for contaminating bacteria to reach the bladder. This study aimed to evaluate the use of antibiotics and the rationality of antibiotic use based on the appropriateness of diagnosis, indication, drug, patient, and dosage. A retrospective descriptive quantitative method was used. The population in this study was all inpatients with a diagnosis of urinary tract infection at Efarina Etaham Pematang Siantar Hospital from January to March 2024. The sample in this study was all medical records and prescriptions of inpatients with a diagnosis of UTI at Efarina Etaham Pematang Siantar Hospital from January to March 2024. The antibiotics used were ceftriaxone and cefixime from the cephalosporin group, and ofloxacin from the quinolone group. The most frequently used antibiotic was cefixime from the cephalosporin group. The results showed that the appropriateness of diagnosis was 100%, indication was 100%, drug was 100%, patient was 100%, and dosage was 100%.